Histochemical Studies on Mesenteric Lymph Nodes in Pre- and Post-Natal Age-Groups of Sheep (Ovis aries) - Jarsangi, Bhagyalakshmi; Kattiannan, Balasundaram; Mannem, Sravanthi; Karnam, Mohan Sujana; Vutharamalluru, Gnani Charitha (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This study investigated the histochemical properties of mesenteric lymph nodes from 36 sheep. Tissues were processed for cryosections  to analyze various biochemical components including glycogen, mucopolysaccharides (acid and neutral), protein tyrosine, lipids and  enzymes like alkaline and acid phosphatases. In prenatal specimens, lipid storage was evident with moderate periodic acid-Schiff (PAS)  activity indicating glycogen presence, alongside moderate activity for acid and neutral mucopolysaccharides in the capsule across all  groups, as evidenced by combined Alcian blue-PAS staining. Tyrosine showed moderate reactivity in the stroma and parenchyma, with  lipid deposits primarily in the capsule. Enzymatic activity was generally weak in the capsule but moderate in the parenchyma. In postnatal  specimens, moderate PAS activity was observed in the capsule, trabeculae and germinal centers, signifying glycogen presence. Alcian  blue-PAS staining indicated strong activity for mucopolysaccharides in the capsule. Tyrosine and lipid reactivities ranged from weak  to strong across different regions, with variable enzymatic activities noted in anatomical regions of the lymph nodes. These findings  highlight significant histochemical differences in mesenteric lymph nodes between prenatal and postnatal age groups of sheep, with  implications for understanding lymphatic biochemical dynamics across developmental stages.
Keywords: Histochemistry; Mesenteric lymph node; Postnatal; Prenatal; Sheep